Fully Depleted Self‐Aligned Heterosandwiched Van Der Waals Photodetectors. Issue 39 (25th August 2022) - Wang, Fang; Liu, Zhiyi; Zhang, Tao; Long, Mingsheng; Wang, Xiuxiu; Xie, Runzhang; Ge, Haonan; Wang, Hao; Hou, Jie; Gu, Yue; Hu, Xin; Song, Ze; et al.
Abstract: Room‐temperature‐operating highly sensitive mid‐wavelength infrared (MWIR) photodetectors are utilized in a large number of important applications, including night vision, communications, and optical radar. Many previous studies have demonstrated uncooled MWIR photodetectors using 2D narrow‐bandgap semiconductors. To date, most of these works have utilized atomically thin flakes, simple van der Waals (vdW) heterostructures, or atomically thin p–n junctions as absorbers, which have difficulty in meeting the requirements for state‐of‐the‐art MWIR photodetectors with a blackbody response. Here, a fully depleted self‐aligned MoS2 ‐BP‐MoS2 vdW heterostructure sandwiched between two electrodes is reported. This new type of photodetector exhibits competitive performance, including a high blackbody peak photoresponsivity up to 0.77 A W −1 and low noise‐equivalent power of 2.0 × 10 −14  W Hz −1/2, in the MWIR region. A peak specific detectivity of 8.61 × 10 10  cm Hz 1/2  W −1 under blackbody radiation is achieved at room temperature in the MWIR region. Importantly, the effective detection range of the device is twice that of state‐of‐the‐art MWIR photodetectors. Furthermore, the device presents an ultrafast response of ≈4 µs both in the visible and short‐wavelength infrared bands. These results provide an ideal platform for realizing broadband and highly sensitive room‐temperature MWIR photodetectors. Abstract : A novel metal‐mirror‐enhanced n–p–n van der Waals heterostructure is designed. The device exhibits excellent performance including high blackbody photoresponsivity up to 0.77 A W −1, high specific detectivity of 8.61 × 10 10 cm Hz 1/2 W −1 under blackbody radiation, and fast response speed of ≈4 µs.